2009
DOI: 10.1097/mot.0b013e32832917b3
|View full text |Cite
|
Sign up to set email alerts
|

Cash, rewards, and benefits in organ transplantation: an open letter to Senator Arlen Specter

Abstract: The amendment would have unintentional negative consequences that could undermine, rather than strengthen, the national and international organ transplant endeavor. These concerns are considered in my personal correspondence to Senator Specter's office on which the text is based.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…These findings mirror the controversy in the literature regarding incentivized organ donation. While some authorities have suggested that incentives will increase living donation and will curtail rampant commercialization, others are concerned that they will lead to coercion and exploitation of the poor [17,21,[49][50][51][52][53].…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
See 2 more Smart Citations
“…These findings mirror the controversy in the literature regarding incentivized organ donation. While some authorities have suggested that incentives will increase living donation and will curtail rampant commercialization, others are concerned that they will lead to coercion and exploitation of the poor [17,21,[49][50][51][52][53].…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…The subject of payment, whether in the form of incentives, rewards or compensation for living donation, is a highly controversial topic that has been debated among experts in the field of transplantation. Some authorities believe that any payment will have negative consequences leading to commercialization and would undermine transplant efforts [17][18][19]. Others have suggested that providing incentives or removing disincentives for organ donation will lead to an increase in organ donation [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little debate that a living donor kidney provides significant financial value to ESRD patients and society—objections to compensation for donors concern whether commodification of the living donor by financial compensation is ethical . Global kidney exchange offers a mechanism for reimbursing the value of a donated kidney without commodification of the donor.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, to date, meaningful discussion has been derailed by | 2511 AJT SEMRAU And MATAS arguments that: fail to engage with the proposal; conflate it with the unregulated, underground trade that is universally condemned; and offer rhetoric in place of evidence-based argument. [12][13][14][15][16][17][18][19][20] By identifying these problematic arguments, we hope to steer the conversation in a more productive direction.…”
Section: Barrier S To a Ss E Ss Ing The Prop Os Ed Sys Temmentioning
confidence: 99%